Union politicization in Sri Lanka: Dimensions and measurement - K.A.S., Dhammika; Ahmad, Fais; Thi, Lip Sam (Department of Business Management, 2013)
Through trade unions are mostly viewed as employee organizations protecting employee"s interests, they have political dimension too. Politicization of employee unions has added an extra complexity not only to their behavior, but also to their impact on organizations in industrial relations. Therefore, this political dimension of employee unions has to be taken into account in studies on unions.Researchers have identified two dimensions of union politicization namely political instrumentality and political ideology. Measurement of union politicization should incorporate both the political instrumentality and political ideology dimensions of union politicization.However, past researches have used either the political instrumentality or political ideology in measuring union politicization depending on their research context.The aim of this study is to test the goodness of measure of the union politicization in Sri Lankan Context. 61 Data was collected from 136 public sector employee selected using stratified random sampling. Exploratory factor analysis and reliability testing were applied for testing the validity and reliability of the measurement. It was found that both political instrumentality and political belief dimensions are validly and reliably held in explaining the union politicization in Sri Lankan context. Further, results and implications are discussed so that it can be used for future research on union politicization.